TECHNOLOGY MANAGEMENT PROCESS FRAMEWORK - Yamamoto, Ikura; Pujotomo, Darminto (J@ti Undip : Jurnal Teknik Industri, 2006)
The effective management of technology as a source of competitive advantage is of vital importance for many organizations. It is necessary to understand, communicate and integrate technology strategy with marketing, financial, operations and human resource strategies. This is of particular importance when one considers the increasing cost, pace and complexity of technology developments, combined with shortening product life cycles. A five process model provides a framework within which technology management activities can be understood: identification, selection, acquisition, exploitation and protection. Based on this model, a technology management assessment procedure has been developed, using an ``action research’’ approach. This paper presents an industrial case study describing the first full application of the procedure within a high-volume manufacturing business. The impact of applying the procedure is assessed in terms of benefits to the participating business, together with improvements to the assessment procedure itself, in the context of the action research framework. Keyword: Technology, Strategy, Management, Assessment